Remote Learning Facilitated by MyScope Explore. (November 2021) - Holmes, Natalie P.; Griffith, Matthew J.; Barr, Matthew G.; Nicolaidis, Nicolas C.; Bhatia, Vijay; Duncan, Michael; McCarroll, Ingrid; Whiting, Jenny; Dastoor, Paul C.; Cairney, Julie M.
Abstract : Abstract: In response to the requirements imposed by the COVID-19 pandemic in 2020, we developed a remote learning undergraduate workshop for 44 students at the University of Newcastle by embedding scanning electron microscope (SEM) images of Maratus (Peacock) spiders into the MyScope Explore environment. The workshop session had two main components: 1) to use the online MyScope Explore tool to virtually image scales with structural color and pigmented color on Maratus spiders; 2) to join a live SEM session via Zoom to image an actual Maratus spider. In previous years, the undergraduate university students attending this annual workshop would enter the Microscopy Facility at the University of Newcastle to image specimens with SEM; however, in 2020 the Microscopy Facility was closed to student visitors, and this virtual activity was developed in order to proceed with the educational event. The program was highly successful and constitutes a platform that can be used in the future by universities for teaching microscopy remotely.